Oddziaływanie polityki naukowej na spółdzielczy sektor mleczarski w województwie mazowieckim - Soliwoda, Michał (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
The impact of science policy on the cooperative dairy sector in Mazovian Voivodeship was assessed in the paper. The link between science policy and other policies: industrial, food and regional one, was analyzed. In the case study the impact of science policy on District Dairy Cooperative in Grodzisk Mazowiecki was assessed. The most important problems that hinder effective interaction of instruments of science policy were presented. The most likely scenario concerning the impact of science policy on the cooperative dairy sector in Mazovia in 5 years was described